PERLINDUNGAN HUKUM KONSUMEN TERHADAP PRODUK MAKANAN YANG DIPASARKAN PELAKU USAHA MENURUT UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 8 TAHUN 1999 - Eka Dharma Yuda, I Dewa Gede; Rudy, Dewa Gde; Putrawan, Suartra (Kertha Semaya : Journal Ilmu Hukum, 2014)
Responsibility of business operators in the event of loss of the food products that are marketed to the consumer is responsible for the losses suffered absolute consumer , either health problems or death caused by ingestion of food or beverage products that are toxic or hazardous . Damages can be referred to health care and the provision of compensation to injured consumers or their heirs or agreement of the parties themselves . Measures manufacturers or businesses that are not responsible to cause harm to consumers . It is stipulated in Article 7 of the Law of the Republic of Indonesia No. 8 of 1999 on Consumer Protection . Legal sanctions against the perpetrators of large-scale food and beverage industry households proved to have violated the use of hazardous substances in the production process is done in the form of withdrawal of food and beverage products , stopping production temporarily to overcome the problem related to the withdrawal of a number of food and household industries , the destruction of food and drinks if proven harmful to human health and life , and revocation of production licenses or business licenses.
Keywords: Protection Laws, Consumer, Food Products, Business Actor